ANALISIS INTERTEKSTUAL UNSUR KEISLAMAN WAWACAN AMIR HAMZAH - Putra, Emil Eka (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2016)
This research is aimed at describing the intertextuality of Wawacan Amir Hamzah and Islamic discourse. The wawacan is seen as a product of intertextuality of previous text which is already exist. This research is conducted by finding meaningful relationships between text of wawacan Amir Hamzah and Muhammad Hussein Haekal’s Sira Nabawiyah. The relationship is seen from the characterization point of view. After the analysis it is found that the main character of the wawacan refers to Hamzah in Sira Nabawiyah. The character, however, in the wawacan is modified by adding some royal attribute and magical power to it. The characters’ action also show some intertextuality of the wawacan and Islamic Discourse. It can be seen from the charcters’ activity such as wudhu, sholat and saying basmalah prior to doing something.Key words: intertextuality, wawacan Amir Hamzah, structuralism